Bulletin NGO = Bulletin ONG (Bruxelles: UAI)
"Union of International Associations. Service Centre for international non-governmental organizations = Union des Associations Internationales. Centre de Service pour les organisations non-gouvernementales Bibliotheek Camille HuysmansAndere titel: (1950): Union des Associations Internationales = Union of International Associations"